2015
DOI: 10.1016/j.toxicon.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of the Amazon coral Micrurus spixii snake venom: Isolation of a new neurotoxic phospholipase A2

Abstract: The Micrurus genus is the American representative of Elapidae family. Micrurus spixii is endemic of South America and northern states of Brazil. Elapidic venoms contain neurotoxins that promote curare-mimetic neuromuscular blockage. In this study, biochemical and functional characterizations of M. spixii crude venom were performed and a new neurotoxic phospholipase A2 called MsPLA2-I was isolated. M. spixii crude venom caused severe swelling in the legs of tested mice and significant release of creatine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 64 publications
5
14
0
6
Order By: Relevance
“…The venom of Viperidae snakes, in general, exhibit more pronounced leishmanicidal activity than that exhibited by B. marajoensis venom [35,70,71]. Both enzymatically inactive and active PLA 2 s from bothropic venoms have shown activity against several species of Leishmania similar to the present study [27][28][29][30]37].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The venom of Viperidae snakes, in general, exhibit more pronounced leishmanicidal activity than that exhibited by B. marajoensis venom [35,70,71]. Both enzymatically inactive and active PLA 2 s from bothropic venoms have shown activity against several species of Leishmania similar to the present study [27][28][29][30]37].…”
Section: Discussionsupporting
confidence: 78%
“…A value greater than 10 is desired for drugable bioactives [76]. Similar results for antiplasmodial activity were found for PLA 2 s from venoms of other snakes of the Viperidae family, including B. asper, C. d. cumanensis and Micrurus spixii [33][34][35]. Quintana et al [34] showed the ratio of hemolytic activity and antiplasmodial activity by means of an indirect hemolysis test.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They concluded that the latter were the most important cause of the neuromuscular blockade. A catalytic phospholipase A 2 from M. s. spixii venom appears to present a similar picture, although there is insufficient information to draw any firm conclusions [182]. Carvalho et al [183] demonstrated that in cultured rat primary hippocampal cells, two PLA 2 s isolated from Micrurus l. lemniscatus venom induced cell death, exhibiting elements of apoptosis, autophagy, and necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their functional versatility and role in myotoxicity, many studies have researched compounds to aid in the treatment of snakebites to inhibit the toxic effects of PLA 2 , as well as to isolate and characterize new PLA 2 s (Carvalho et al, 2013;Da Silva et al, 2009;Terra et al, 2015). The combination of two chromatographic steps: size exclusion and RP-HPLC, widely used for purification of PLA 2 s (Damico et al, 2005(Damico et al, , 2012Martins et al, 2014), effectively isolated ColTx-I.…”
Section: Discussionmentioning
confidence: 99%